2017
DOI: 10.22456/1982-8918.73193
|View full text |Cite
|
Sign up to set email alerts
|

Um Estudo Exploratório Da Tendência “Antiobesidade” Entre Professores E Estudantes De Educação Física Italianos

Abstract: Resumo: O objetivo desta pesquisa foi analisar as atitudes implícitas e explícitas sobre a obesidade em professores e estudantes de Educação Física. Dezoito professores e 45 estudantes preencheram quatro questionários: o Teste de Associação Implícita (IAT), que avalia por meio de categorizações os estereótipos e as associações cognitivas espontâneas; o questionário de Crandall para a avaliação do preconceito explícito sobre a obesidade; a Escala sobre a Orientação à Dominância Social (SDO); e o Questionário de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
4
0
3
Order By: Relevance
“…For instance, O'Brien et al (2007) administered the AFA to a sample of trainee PE teachers and found that the mean (M) score obtained on the Dislike subscale was 1.5 standard deviation (SD) below the midpoint of the scale, indicating a pro-fat attitude of the trainees in the sample. Similar results have been found by Gago et al (2012) and Gobbi et al (2017) using the same measure (1.3 and 1.2 SD below the midpoint, respectively) and by Alameda and Whitehead (2015) and Rukavina et al (2019) using the Disparagement subscale of the AFAT (2.0 and 1.8 SD below the midpoint, respectively).…”
Section: Do Physical Education (Pe) Teachers Have An Anti-fat Bias?supporting
confidence: 86%
See 4 more Smart Citations
“…For instance, O'Brien et al (2007) administered the AFA to a sample of trainee PE teachers and found that the mean (M) score obtained on the Dislike subscale was 1.5 standard deviation (SD) below the midpoint of the scale, indicating a pro-fat attitude of the trainees in the sample. Similar results have been found by Gago et al (2012) and Gobbi et al (2017) using the same measure (1.3 and 1.2 SD below the midpoint, respectively) and by Alameda and Whitehead (2015) and Rukavina et al (2019) using the Disparagement subscale of the AFAT (2.0 and 1.8 SD below the midpoint, respectively).…”
Section: Do Physical Education (Pe) Teachers Have An Anti-fat Bias?supporting
confidence: 86%
“…In general, the results of these studies show that most PE teachers maintain implicit obesity biases (Alameda and Whitehead, 2015;Gago et al, 2012;Gobbi et al, 2017;Fontana et al, 2013;Lynagh et al, 2015;O'Brien et al, 2007). For example, Fontana et al (2013), using a pencil and paper version of the Implicit Association Test (IAT) to measure the automatic associations between the concepts thin/fat with the attributes good/bad and lazy/active, found, both in teachers and trainee teachers, that the fat-bad and fat-lazy associations were much stronger than the fatgood and fat-active associations.…”
Section: Do Physical Education (Pe) Teachers Have An Anti-fat Bias?mentioning
confidence: 95%
See 3 more Smart Citations